The determination of stability constants of N-acetyl-L-cysteine chrome, nickel, cobalt and iron complexes by potentiometric method - (:unkn) unknown (ELSEVIER SCIENCE SA, 1998)
The stability constants of the complexes which were formed N-acetyl-L-cysteine (NAC) with chrome(III), nickel(II), cobalt(II), iron(III) were determined using Irwing-Rossotti method, in this work. The protonation constants and dissociation constants of the ligand were found as log k(1) = pk(2) = 9.60; log k(2) = pk(1) = 2.70 at 25 degrees C and for I = 0.12 and log k(1) = pk(2) = 9.30; log k(2) = pk(1) = 2.70 at 37 degrees C and for I = 0.12. Also the overall formation constants of complexes were found as log beta(2) = 7.80 for cobalt(II); as log beta(2) = 15.00 for chrome(III); as log beta(2) = 9.34 for nickel(II); and as log beta(2) = 18.80 for iron(III); at 37 degrees C and I = 0.12. The conditional formation constants and the formation pH ranges of complexes were determined. Relative abundance was plotted using conditional formation constant and the steps of the formation of the complexes were shown in graphs. As can be seen from the results, the formation constants of the complexes of Cr(III) and Fe(III) with NAC are considerably higher than those of Ni(II) and Co(II) complexes. (C) 1998 Elsevier Science S.A. All rights reserved.
Keywords: stability constants; potentiometric titration; N-acetyl-L-cysteine; cobalt(II); chrome(III); iron(III); nickel(II); ACETYLCYSTEINE; ZINC